First Principles Computational Study of Surface Reactions Toward Design Concepts of High Functional Electrocatalysts for Oxygen Reduction Reaction in a Fuel Cell System - Hwang, Jeemin; Noh, Seunghyo; Kang, Joonhee; Han, Byungchan (Biuletyn Uniejowski, 2017)
Design of novel materials in renewable energy systems plays a key role in powering transportation vehicles and portable electronics. This review introduces the research work of first principles-based computational design for the materials over the last decade to accomplish the goal with less financial and temporal cost beyond the conventional approach, especially, focusing on electrocatalyst toward a proton exchange membrane fuel cell (PEMFC). It is proposed that the new method combined with experimental validation, can provide fundamental descriptors and mechanical understanding for optimal efficiency control of a whole system. Advancing these methods can even realize a computational platform of the materials genome, which can substantially reduce the time period from discovery to commercialization into markets of new materials. KCI Citation Count: 0